Dietary supplementation of exopolysaccharides from Lactobacillus rhamnosus GCC-3 improved the resistance of zebrafish against spring viremia of carp virus infection - Xie, Mingxu; Li, Yu; Olsen, Rolf Erik; Ringø, Einar; Yang, Yalin; Zhang, Zhen; Ran, Chao; Zhou, Zhigang (Frontiers in Immunology, 2022)
Spring viremia of carp virus (SVCV) can cause high mortality of fish. In this study, we investigated the effects of Lactobacillus rhamnosus GCC-3 exopolysaccharides (GCC-3 EPS) on zebrafish infected with SVCV and elucidated the underlying mechanisms. Zebrafish were fed with a control diet or diet supplemented with 0.5% and 1% of GCC-3 EPS for 2 weeks. At the end of the feeding regime, zebrafish were challenged by SVCV and the antiviral immune response in the spleen was evaluated on the 4th day post SVCV infection. Zebrafish embryonic fibroblast (ZF4) cells were treated with GCC-3 EPS. Small interfering RNA (siRNA) was used to knock down TANK-binding kinase 1 (TBK1) in ZF4 cells. Gut microbiota was analyzed after 3 weeks of feeding. Results showed that dietary 0.5% and 1% GCC-3 EPS significantly improved the survival rate of zebrafish compared with the control group. In addition, dietary 0.5% and 1% GCC-3 EPS significantly up-regulated the expression of genes related to type I interferon (IFN) antiviral immunity. Consistent with in vivo results, GCC-3 EPS significantly inhibited SVCV replication in ZF4 cells while significantly increased the expression of type I IFN signaling pathway related genes. Furthermore, knocking down TBK1 significantly blocked the antiviral effect of GCC-3 EPS. Moreover, dietary GCC-3 EPS improved gut microbiota, and the culture supernatant of GCC-3 EPS-associated microbiota significantly inhibited SVCV replication in ZF4 cells compared with the control-microbiota counterpart. In conclusion, our results indicate that dietary GCC-3 EPS can improve the resistance of zebrafish against SVCV infection, and the mechanism may involve enhanced type I interferon signaling.